Enhanced electrodegradation of the Sunset Yellow dye in acid media by heterogeneous Photoelectro-Fenton process using Fe3O4 nanoparticles as a catalyst. Issue 1 (February 2020) - Pinheiro, Amanda C.N.; Bernardino, Tayná S.; Junior, Fausto E.B.; Lanza, Marcos R.V.; Barros, Willyam R.P.
Graphical abstract: Highlights: Fe3 O4 nanoparticles were used as a heterogeneous catalyst. The dye was degraded by photo electro-Fenton and solar Photoelectro-Fenton process. Fe 2+ ions were used as a catalyst for the electrodegradation process. The dye was significantly removed by solar Photoelectro-Fenton process. Fe3 O4 nanoparticles were reused for 8 consecutive cycles of degradation. Abstract: This work describes the study of sunset yellow (SY) dye degradation based on the heterogeneous electro-Fenton (EF) process, where Fe3 O4 NPs were used as heterogeneous catalysts. The electrochemical system used was an undivided electrochemical cell with single compartment and a gas diffusion electrode (GDE) was used as a working electrode. The SY dye samples were analyzed by UV–vis spectrophotometry, high performance liquid chromatography (HPLC) and total organic carbon (TOC). Fe3 O4 NPs were synthesized by co-precipitation method and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and N2 -physisorption analysis. For the Photoelectro-Fenton (PEF) process, the concentration decay of SY dye was 80 and 99 % in the presence of 0.1 mol L −1 Na2 SO4 and 0.13 mol L −1 NaCl respectively. The results of TOC removal, showed that ∼50 % of mineralization was achieved at 90 min. For the solar Photoelectro-Fenton process (SPEF) there was high catalytic yield, i.e., 98.7 % of color removal, 100 % of concentration decay and 71 % of TOC removal at 90 min. of electrolysis. The Fe3 O4 NPs stability was confirmed after eight consecutive degradation cycles, showing that there is no loss of catalytic activity at the end of the last cycle. The results obtained by XRD analysis showed that there was no structural alteration in the crystallography of the NPs after 5 h of degradation in both electrolytes. There was no dissolution of Fe 2+ ions at the end of electrolysis when the SY dye was subjected to the degradation by EF, PEF and SPEF processes.